SYSTEMATIZATION OF THE BASIC STEPS OF THE STEP-AEROBICS - Darinka Korovljev; Milena Mikalački; Nebojša Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Following the development of the powerful sport industry, in front of us appeared a lot of new opportunities for creating of the new programmes of exercising with certain requisites. One of such programmes is certainly step-aerobics. Step-aerobics can be defined as a type of aerobics consisting of the basic aerobic steps (basic steps) applied in exercising on stepper (step bench), with a possibility to regulate its height. Step-aerobics itself can be divided into several groups, depending on the following: type of music, working methods and adopted knowledge of the attendants. In this work, the systematization of the basic steps in step-aerobics was made on the basis of the following criteria: steps origin, number of leg motions in stepping and relating the body support at the end of the step. Systematization of the basic steps of the step-aerobics is quite significant for making a concrete review of the existing basic steps, thus making creation of the step-aerobics lesson easier